2006
DOI: 10.1097/01.inf.0000202067.50975.90
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Kawasaki Disease in Infants Younger than Six Months of Age

Abstract: Infants younger than 6 months with prolonged unexplained febrile illnesses should be suspected as having Kawasaki disease, despite the incomplete clinical presentation. Because early diagnosis and timely treatment are difficult in younger infants with Kawasaki disease because of delayed and incomplete clinical presentations, echocardiogram becomes an important implement for diagnosis. Early intravenous immunoglobulin treatment is required in view of the highest risk of coronary involvement in them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
111
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 18 publications
12
111
2
3
Order By: Relevance
“…10 Given that the presence of CAD is a very restrictive and specific criterion of incomplete KD, the AHA has developed an algorithm with clinical and analytical criteria for the evaluation and treatment of patients in whom incomplete KD is suspected, which we have used as a gold standard in this study. As in other studies, 11 we have found a longer diagnostic delay in incomplete forms, which, in our case, has been 24 hours (7 versus 6 days) and that in incomplete forms could be related to a higher risk of developing CAD. In our series, CRP and albumin levels have been related to the risk of developing CAD, as observed in other studies.…”
Section: Discussionsupporting
confidence: 66%
“…10 Given that the presence of CAD is a very restrictive and specific criterion of incomplete KD, the AHA has developed an algorithm with clinical and analytical criteria for the evaluation and treatment of patients in whom incomplete KD is suspected, which we have used as a gold standard in this study. As in other studies, 11 we have found a longer diagnostic delay in incomplete forms, which, in our case, has been 24 hours (7 versus 6 days) and that in incomplete forms could be related to a higher risk of developing CAD. In our series, CRP and albumin levels have been related to the risk of developing CAD, as observed in other studies.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, unusual symptoms, including aseptic meningitis, appear to occur more frequently in this age group 9) . It is plausible that the infrequent occurrence of typical signs of KD in affected infants is secondary to an inadequate immune response, which results in the weak vas culitis phenomenon observed in this age group 10) . Alternative explanations for the occurrence of incomplete KD in infants include the effect of superan tigen neutralization by maternal antibodies, transferred via the placenta, or cross reaction of antibodies gene rated by frequent active immunization 10) .…”
Section: Discussionmentioning
confidence: 99%
“…1,7 Incomplete cases are patients who do not fulfill the diagnostic criteria but have fever and two or three criteria and often have coronary involvement; Case Challenge previous studies showed a higher incidence of coronary abnormalities in infants younger than 6 months. 1 The diagnosis of IKD is difficult because many other infectious and inflammatory conditions may mimic its manifestations, such as Epstein-Barr virus infection and scarlet fever.…”
Section: Discussionmentioning
confidence: 99%
“…6 The diagnosis in this age of group is difficult because the clinical picture is often incomplete and similar to other diseases. 7 …”
Section: Diagnosismentioning
confidence: 99%